Any Where Vote: ATM as Evm. Issue 1 (January 2021) - Devi, A. Sangeerani; Chinnasamy, A.; Kavitha, D.; Shali, A.
Abstract: The Election Commission has been using them anual system during elections to vote in the digitization of this modern age. In all Elections (Presidential), electronic voting machines (EVMs) are be introduced, although they are not fully automated and have many limitations. And Moreover, every election is decided by those who show up. The main idea is to build a system that modifies the ATM's (Automated Teller Machine) system to work as EVM (Electronic Voting Machine) during the elections dates. This will allow to facilitate the election process for any voter in India to cast the vote to their respective constituency from anywhere in India by going to the nearest ATM in his/her location. When the voter inserts his/her ATM card, a voting option will be enabled for casting the vote. When the voter selects the voting option, they have to pass through a 2-level authentication procedure.. Then, the user is allowed to cast his vote by selecting a political candidate from a list of political parties of that constituency. Again, authentication will be asked before casting vote. Whenitiscompletedthecount in that unique hash value is incremented and the voting access to the user will be disabled for the particular voter. All votes are stored directly in the Electoral Commission main database. Kerberos Authentication Server and Voting Card Database is used for voting and authentication process.